Determinants of iodine deficiency among school age children in Guraghe Zone, Southwest Ethiopia - Berhanu Abebaw; Abdu Oumer (International Journal of Public Health Science (IJPHS), 2020)
Globally, insufficient iodine intake is found to be the most common preventable cause of mental retardation that results in diminished immunity, decreased school performance and infant and young child death. Ethiopia is the first of the top iodine deficient countries in the world. About 12 million children (school age) get inadequate iodine. Community based cross sectional study was conducted on 792 school age children in Guraghe Zone, Ethiopia to assess the determinants of iodine deficiency. Multistage sampling technique was used to select the study subjects. Data were collected by using pretested questionnaire. Clinical examinations were taken following standard procedures. The collected data were entered into Epi-data and exported to SPSS for analysis. Descriptive statistics was calculated and presented accordingly. Bivariate and multivariable Logistic regression with odds ratios along with the 95% confidence interval was computed and interpreted accordingly. A P-value <0.05 was declared as statistically significant association. Total goiter rate was 8.7%. Factors that had significant association with goiter were: School age children who utilized non iodized salt (AOR=3.12, 95% CI=1.73-5.63), those who consumed cabbage >2 times per week (AOR=1.94, 95% CI=1.10-3.52), and children who got elder (AOR=1.22, 95% CI=1.10-1.41). The study area had mild iodine deficiency disorder. Non iodized salt utilization; frequent cabbage consumption and increased age of children were found to be predictors of goiter. Thus, Interventions should focus on universal salt iodization, besides familiarizing goiterogens to the community at large.